Pemberdayaan Perempuan sebagai Bentuk Penguatan Strategi Pengarusutamaan Gender dalam Situasi Bencana di Kabupaten Klaten - Nur Hafida, Siti Hadiyati (Jurnal SOLMA, 2019)
Gender problems are one of the problems that arise during a disaster. Women's are often seen as weak communities so women's roles when pre, current and post-disaster situations are very minimal. The condition of vulnerability to disasters more is further aggravated in the post-disaster period. Women who are victims of disasters often have not received special attention in the refugee camps. This is because the role of women in post-disaster conditions is still very minimal. The involvement of women only at the stage of managing foodstuffs besides that, women that involved are not women victims of the disaster but volunteers. Women can empower communities in disasters because of the skills and capacities of women when doing domestic activities at home (caring for children, washing, cleaning the house, etc.). Based on the conditions in Klaten Regency, there needs to be socialization and education regarding the importance of the gender mainstreaming strategy in disasters, especially post-disaster period. Dissemination and education to strengthen the gender mainstreaming strategy is carried out by providing material on trauma healing due to disasters through songs. Women have the ability as caregivers who are better than men, therefore empowering women when a post-disaster situation becomes an aspect that needs attention in the disaster management cycle.